A tunable single-mode double-ring quantum-cascade laser - Dhirhe, D.; Slight, T.; Nshii, C.; Ironside, Charlie (2012)
The design, fabrication and characterization of a monolithic double-ring quantum- cascade laser (DRQCL) are described. At a wavelength of 4.6m, we demonstrate tunable, single-mode operation of a DRQCL and use it as a source for spectroscopy of CO gas.